108k views
4 votes
An equation is shown below: 2(3x − 5) = 1 Which of the following correctly shows the first two steps to solve this equation? Step 1: 6x − 10 = 1; Step 2: 6x = 11 Step 1: 6x − 5 = 1; Step 2: 6x = 6 Step 1: 5x − 3 = 1; Step 2: 5x = 4 Step 1: 5x − 7 = 1; Step 2: 5x = 8

2 Answers

3 votes

Answer: The correct answer is "Step 1: 6x − 10 = 1; Step 2: 6x = 11"

Explanation:

User Mustapha El Kojji
by
6.8k points
6 votes

Answer:

A: Step 1: 6x − 10 = 1; Step 2: 6x = 11

Explanation:

First: remove parentheses by multiplying factors.

6x - 10 = 1

Second: Move the constants to the right side of the equation

6x = 1 + 10

6x = 11

User Vinit Prajapati
by
6.2k points